Dinamika Ekspektasi dalam Pasangan Berpacaran: Studi pada Akun TikTok @ashleywrobz - Bhudiawan, Michelle Angela; Junaidi, Ahmad (Koneksi, 2025)
This study aims to analyze the role of TikTok content from the account @ashleywrobz in shaping expectations about romantic relationships, particularly among the younger generation. The expectations discussed are based on the uses and gratifications theory, which explains the motivation and gratification of media users, as well as the interpersonal communication elements by Joseph Devito, namely openness, empathy, supportiveness, positivity, and equality. This study employs a qualitative approach with a case study method to explore users’ perceptions and experiences related to the content. The findings indicate that TikTok content from @ashleywrobz significantly shapes positive expectations, especially in terms of openness and supportiveness in romantic relationships. However, the expectations formed are often excessive and unrealistic, potentially leading to conflicts or disappointment. This study provides insights into the role of social media as a shaper of romantic expectations while emphasizing the importance of digital literacy to understand and align expectations with reality. Recommendations are offered to individuals, couples, and academics to enhance healthy interpersonal communication and adopt a critical perspective toward digital content. Penelitian ini bertujuan untuk menganalisis peran konten TikTok dari akun @ashleywrobz dalam membentuk ekspektasi pada hubungan berpacaran, terutama di kalangan generasi muda. Ekspektasi yang dibahas meliputi teori uses and gratifications, yang menjelaskan motivasi dan gratifikasi pengguna media, serta elemen komunikasi interpersonal dari Joseph Devito, yaitu keterbukaan, empati, dukungan, rasa positif, dan kesetaraan. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus untuk menggali persepsi dan pengalaman pengguna terkait konten tersebut. Hasil penelitian menunjukkan bahwa konten TikTok @ashleywrobz secara signifikan mampu membentuk ekspektasi positif, terutama pada aspek keterbukaan dan dukungan dalam hubungan berpacaran. Namun, ekspektasi yang terbentuk sering kali berlebihan dan tidak sesuai dengan realitas hubungan, sehingga berpotensi menimbulkan konflik atau kekecewaan. Penelitian ini memberikan wawasan mengenai peran media sosial sebagai pembentuk ekspektasi romantis, sekaligus menekankan pentingnya literasi digital untuk memahami dan menyesuaikan ekspektasi dengan realitas. Saran diberikan kepada individu, pasangan, dan akademisi untuk memperkuat komunikasi interpersonal yang sehat serta bersikap kritis terhadap konten digital.